Hospital discharge planning in care transition of patients with chronic noncommunicable diseases - Sara Maria Barbosa; Fabiana Costa Machado Zacharias; Tatiele Estefâni Schönholzer; Diene Monique Carlos; Maria Estela Lacerda Pires; Silvia Helena Valente; Luciana Aparecida Fabriz; Ione Carvalho Pinto (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze care transition in hospital discharge planning for patients with chronic noncommunicable diseases. Method: a qualitative study, based on the Care Transitions Intervention theoretical model, with four pillars of intervention, to ensure a safe transition. Twelve professionals participated in a public hospital in the countryside of São Paulo. Data were collected through observation, document analysis and semi-structured interviews. Results: there was a commitment of a multidisciplinary team to comprehensive care and involvement of family members in patient care. The documents facilitated communication between professionals and/or levels of care. However, the lack of time to prepare for discharge can lead to fragmented care, impairing communication and jeopardizing a safe transition. Final considerations: they were shown to be important elements in discharge planning composition, aiming to ensure a safe care transition, team participation with nurses as main actors, early discharge planning and family involvement.